2017
DOI: 10.5530/ijper.51.3.77
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antimicrobial Activity of some Metal Complexes Derived from Thiazole Schiff Bases with In-vitro Cytotoxicity and DNA Cleavage Studies

Abstract: Five metal complexes with Schiff-base ligand, 3-((4-phenylthiazol-2-ylimino) methyl)-2-hydroxybenzoic acid were synthesized with metal ions such as Cu(II), Co(II), Ni(II), Cd(II) and Zn(II). The reaction likely proceeds via condensation of 2-amino-4-phenyl thiazole with 3-aldehydosalicylic acid and characterized by elemental analysis and various spectral studies like FT-IR, 1 H NMR, ESI mass, and TGA/TDA and molar conductance studies. The spectral results revealed bidentate O-O donor and forms the complexes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A large number of possibilities of coordination allows to manipulate pharmacological properties of half-sandwich arene-Ru(II) complexes making them ideal candidates for preparing multifunctional drugs. 10,11 Pyrazole and its derivatives demonstrate various biological activities, e.g. antibacterial, antifungal, antiviral, anticancer, anticonvulsant, analgesic, anti-inammatory, anti-diabetic, sedative, anti-rheumatic.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of possibilities of coordination allows to manipulate pharmacological properties of half-sandwich arene-Ru(II) complexes making them ideal candidates for preparing multifunctional drugs. 10,11 Pyrazole and its derivatives demonstrate various biological activities, e.g. antibacterial, antifungal, antiviral, anticancer, anticonvulsant, analgesic, anti-inammatory, anti-diabetic, sedative, anti-rheumatic.…”
Section: Introductionmentioning
confidence: 99%
“…All examined compounds show good antimicrobial activity against the microorganisms. It is observed that the complexes are more active than the free ligand and this activity is promoted on coordination with metal ions . However, the complexes have moderate activity as compared with standards drugs.…”
Section: Resultsmentioning
confidence: 99%
“…According to this concept, liposolubility is considered as an important factor for the cell permeability of the lipid membrane that surrounds the cell favors the passage of only lipid soluble materials which controls the antimicrobial activity of the compounds. On chelation, the overlap of ligand orbital and partial sharing metal ion positive charge with donor atoms present in the ligand reduces the polarity of the metal ion and there may be increase in the π ‐ electrons delocalization over the whole chelating ring system and thus increases the lipophilic character of the metal chelates which also enhances the penetration of the metal complexes to lipid membrane through lipid layer and also the additional factors of conductivity, solubility and bond length between the metal and the ligand increase the activity of metal complexes . The efficiency of the compounds against different organisms depends upon the impermeability of the cells of microorganisms and difference in ribosome of the microbial cells .…”
Section: Resultsmentioning
confidence: 99%